(untitled) (Medical Forum Monthly, 2024)
Objective: Aerial parts of Fagonia Bruguieri (FB) (family, zygophyllaceae) were subjected to in vivo hepatoprotective study in order to validate its traditional use in hepatobiliary disorders, by native people of Cholistan desert, Pakistan. Design of Study: Experimental study. Place of study: This study was conducted at PCR lab Multan. Materials & Methods: The animals were randomly divided into three groups, containing 10 rabbits in each group. Hepatoprotective effects of pre-treatment with aerial parts (ethanolic extract) of FB (500 and 750 mg/kg/day PO for 7 days) against CCl4 (0.75 ml/kg, S/C) intoxicated rabbits were evaluated by serum biochemical parameters and liver histological observations. Silymarin (100 mg/kg/day PO for 7 days) was used as a standard hepatoprotective drug, Results: CCl4 intoxicated group had raised levels of SGOT, SGPT and ALP sTignificantly but TB level was not raised as compared to normal control group. FB extract (both doses of 500 and 750 mg/kg) showed hepatoprotection as obvious by significant reinstatement of levels of SGOT, SGPT and ALP while TB level was not changed significantly, when compared with CCl4 intoxicated group. Both doses of FB extract were well comparable with silymarin. Histopathological examination of the liver tissue further corroborated these results. Conclusion: Therefore, the conclusion of the present study supports the traditional believes on hepatoproptective effects of Fagonia Bruguieri (aerial parts).